Effect of Cs atoms adsorption on the work function of the LaB6 (100) surface - Huaqing Zheng; Xin Zhang; Jun Hu; Yuhong Xu; Guangjiu Lei; Sanqiu Liu; Heng Li; Zilin Cui; Yiqin Zhu; Xiaolong Li; Xiaoqiao Liu; Shaofei Geng; et al. (Nuclear Materials and Energy)
This study used first-principles density functional theory with cp2k and VASP software to investigate the effects of Cs atoms adsorption on the work function of the LaB6 (100) surface. The results indicate that the most stable adsorption site for Cs atoms is at the top of the B atoms. The adsorption energy of Cs atoms was decomposed into three parts. The binding energy of the Cs layer on the deformed substrate has the largest contribution to the total adsorption energy and plays a dominant role. Although LaB6 is considered a potential Cs-free material, we found that Cs atom adsorption further lowers the surface work function compared to a clean LaB6 (100) model, facilitating electron emission. The change in work function is influenced by the dipole moment and is linearly related to changes in the dipole moment. Additionally, in systems with Cs atom adsorption, the charge rearrangement effect (Δp) dominates changes in the total dipole moment. These results provide some reference for the selection of fusion plasma gird materials and the production of hydrogen negative ion sources for neutral beam injection.